Seasonal Variability of QT Dispersion in Healthy Young Males - Kose, Sedat (Ann Noninvasive Electrocardiol, 2003)
Background: There are few data related to the seasonal influences on the QT dispersion. Methods: We analyzed the effects of seasons on QT dispersion in a large group of healthy young males. We studied the seasonal variability of QT dispersion in 523 healthy male subjects aged 22 ± 4 years (ranging from 20 to 26). Four seasonal 12‐lead resting electrocardiograms (ECGs) recorded at double amplitude were performed at 25 mm/s at intervals of 3 months. Subsequent ECGs were recorded within 1 hour of the reference winter recording. QT dispersion was defined as the difference between the longest and the shortest mean QT intervals. Results: There was a significant seasonal variation in QT dispersion (P = 0.001), with the largest QT dispersion in winter (71 ± 18 ms) and the smallest one in spring (43 ± 19). Conclusion: There exists a significant seasonal variation in QT dispersion of healthy subjects and such variability should be taken into consideration in the evaluation process of QT dispersion.